Tarski's influence on computer science - Feferman, S. (20th Annual IEEE Symposium on Logic in Computer Science (LICS' 05), 2005)
Summary form only given. The great logician Alfred Tarski played one of the leading roles in the development of mathematical logic in the twentieth century, as much for the programs he promoted and the conceptual organization of the subject as for his many important results. Except for his fixed-point theorem, Tarski's influence on computer science has been largely indirect but nevertheless substantial. The author surveys this influence through his work in the areas of decision procedures, semantics of formal languages, model theory, and algebraic logic.